2019
DOI: 10.1186/s12913-019-4428-z
|View full text |Cite
|
Sign up to set email alerts
|

Health care professional’s communication through an interpreter where language barriers exist in neonatal care: a national study

Abstract: Background A number of parents in neonatal care are foreign-born and do not speak the local language, which makes communication between healthcare professionals and parents more difficult. Interpreters can be used when language barriers exist - parent interactions, medical communication and communication about the care of the child . The aim in this study was to examine healthcare professionals’ use of interpreters and awareness of local guidelines for interpreted commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…In fact, this decision is taken by the patients on many pragmatic grounds including the perception of delays, miscommunication, omission, and breach of privacy. These findings are concomitant with studies conducted in the past [ 23 , 25 , 50 ]. The findings also confirm that the communicational and linguistic gap was perceived by the nurses as a major threat to the timely provision of health care [ 23 , 51 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, this decision is taken by the patients on many pragmatic grounds including the perception of delays, miscommunication, omission, and breach of privacy. These findings are concomitant with studies conducted in the past [ 23 , 25 , 50 ]. The findings also confirm that the communicational and linguistic gap was perceived by the nurses as a major threat to the timely provision of health care [ 23 , 51 ].…”
Section: Discussionsupporting
confidence: 88%
“…As to the communicational experiences of the nurses, it can be inferred that everyday interactions are not disturbed by the mere linguistic gap, and the need for the interpreter is required by nurses, depending on to the nature of the disease (e.g., diabetes) or the patient (e.g., newborn). These findings are supported by earlier studies that revealed nurses use mobile apps and gestures to communicate with patients on a daily basis [ 49 , 50 ]. It can be inferred from the findings that opting for an interpreter is not a ritualistic and ubiquitous stage of the caring process.…”
Section: Discussionsupporting
confidence: 87%
“…However, it is reported in the literature that the number of translators is not adequate, and translators are not available at all times, which is similar to the findings of the present study. 26,27,30 In a systematic review, nurses who work with adequate professional interpreters provide better care. It is also reported in previous studies that discharge planning, objective translation, and decision-making process are better when nurses have access to a professional interpreter.…”
Section: Discussionmentioning
confidence: 99%
“…This has been seen in adult primary care and medical subspecialty ambulatory care where non-English speakers had lower rates of telemedicine use [ 11 ]. Patients, parents, and their health care teams may experience barriers in communicating through interpreters, particularly if individuals who are not professional medical interpreters are used to facilitate communication [ 17 , 21 23 ]. The situation can be especially challenging if families’ preferred language is a language of lesser diffusion with limited availability of professional medical interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…For example, low-income level, public insurance, unmarried status, and black race (due to systemic racism in the United States) have been associated with higher risk for preterm birth [ 16 ]. In addition, primary language affects communication between healthcare teams and families, which indirectly impacts newborn care [ 17 ].…”
Section: Introductionmentioning
confidence: 99%